2021
DOI: 10.1038/s41598-021-00071-6
|View full text |Cite
|
Sign up to set email alerts
|

Aronia melanocarpa polysaccharide ameliorates inflammation and aging in mice by modulating the AMPK/SIRT1/NF-κB signaling pathway and gut microbiota

Abstract: Aronia melanocarpa is a natural medicinal plant that has a variety of biological activities, its fruit is often used for food and medicine. Aronia melanocarpa polysaccharide (AMP) is the main component of the Aronia melanocarpa fruit. This research evaluated the delay and protection of AMP obtained from Aronia melanocarpa fruit on aging mice by d-Galactose (D-Gal) induction and explored the effect of supplementing AMP on the metabolism of the intestinal flora of aging mice. The aging model was established by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…Under normal physiological conditions, the combination of Keap1 to Nrf2 protein inhibits Nrf2/HO-1 pathway, while Nrf2 dissociates and translocates into the nucleus to promote the expression of downstream genes after the cells were exposed to oxidative stress. Many previous studies have demonstrated that Nrf2 could directly or indirectly exert antioxidant stress and antiaging function [ 50 52 ]. Hence, it is reasonable to speculate that PA might play a role in antioxidant stress and antisenescent cartilage damage in D-gal-induced aging model by activating the Nrf2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, the combination of Keap1 to Nrf2 protein inhibits Nrf2/HO-1 pathway, while Nrf2 dissociates and translocates into the nucleus to promote the expression of downstream genes after the cells were exposed to oxidative stress. Many previous studies have demonstrated that Nrf2 could directly or indirectly exert antioxidant stress and antiaging function [ 50 52 ]. Hence, it is reasonable to speculate that PA might play a role in antioxidant stress and antisenescent cartilage damage in D-gal-induced aging model by activating the Nrf2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, loss of SIRT3 interacts with the gut microbiota in the NAFLD progression. More importantly, natural polysaccharides regulate the activities of SIRTs, such as SIRT1 and SIRT3, in human diseases ( Dimitrova-Shumkovska et al, 2020 ; Zhao et al, 2021b ). However, the direct evidence that natural polysaccharides protect HFD-induced NAFLD through regulation of SIRTs-mediated gut microbiota is lacking.…”
Section: Hfd-induced Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Another recent report demonstrated that Astragalus polysaccharides can reduce glucose-induced premature senescence and inflammasome activation in rat aortic endothelial cells (Miao et al, 2022 ). Using a d-galactose induced aging mice model, the application of Aronia melanocarpa heteropolysaccharides successfully ameliorated inflammation and aging in mice by modulating the AMPK/SIRT1/NF-κB signaling pathway and gut microbiota (Zhao et al, 2021 ). Studies on polysaccharides isolated from the herb Angelica sinensis have revealed anti-cellular senescence and antioxidant attributes in haematopoietic cells and endothelial progenitor cells while in vivo suppression of cellular senescence and improvement in brain senescence in a murine model of d-galactose induced aging was also observed (Cheng et al, 2019 ; Lai and Liu, 2015 ; Mu et al, 2017 ; Xiao et al, 2017 ).…”
Section: Primary Diet Constituents and Cellular Senescencementioning
confidence: 99%